Relationships between pre-stimulus gamma power and subsequent P300 and reaction time break down in schizophrenia - Reinhart, Robert M.G. (2010)
INTRODUCTION: Little is known about the relationship between gamma-band oscillations prior to the arrival of a target stimulus and subsequent sensory processing and response execution. Although schizophrenia has been associated with abnormalities in gamma-band oscillations, P300, and reaction time (RT), few studies have examined the possible correspondence between these three neurobiological and behavioral markers in schizophrenia. To characterize the relationship between preparatory processes, information processing, and subsequent behavioral performance in schizophrenia, the present study investigated the relationships between pre-stimulus gamma-band power, RT and P300 amplitude. METHODS: EEG and behavioral data were collected from 18 schizophrenia patients and 21 healthy controls during a conventional auditory oddball task. RESULTS: In controls, single-trial pre-stimulus gamma power was positively correlated with RT, and average P300 amplitude was positively correlated with average pre-stimulus gamma power. DISCUSSION: We interpret these findings as evidence that gamma power enhancement reflects a state of greater pre-stimulus preparation resulting in fuller evaluation of the target stimulus and therefore slower RT, as proposed by Jokeit and Makieg (1994). Consistent with previous research, schizophrenia patients exhibited RT slowing and P300 amplitude reductions relative to controls. Importantly, neither RT nor P300 amplitude were related to pre-stimulus gamma power in schizophrenia, suggesting a breakdown in the preparatory brain state critical for stimulus processing and later motor execution. The present findings underscore the behavioral significance of gamma-band responses, and provide an additional link between gamma-band oscillations and information processing abnormalities in schizophrenia.